Educational background, HRD training, and organisational experience effects on employee performance - Sugeng Tri Wuryanto; Setya Raharja (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2026)
This research aims to analyze the influence of educational background, human resource development (HRD) training, and organizational experience on employee performance at Yogyakarta State University (UNY). This study employed a quantitative approach with an explanatory research design. The population comprised 392 employees (Golongan III) at UNY, with a sample size of 198 respondents determined using the Slovin formula and selected via proportionate random sampling. Data were collected using questionnaires that passed validity and reliability tests. The data analysis technique used was multiple linear regression, including t-tests, F-tests, and determination coefficient analysis. The findings indicate that: (1) educational background has a positive and significant effect on employee performance; (2) HRD training has a positive and significant effect; (3) organizational experience has a positive and significant effect; and (4) simultaneously, these three variables significantly influence employee performance with a contribution of 72.67%. Notably, HRD training was identified as the most dominant variable affecting performance. The study recommends that the university prioritize competency-based training and integrate organizational experience into career development paths.